Maximizing Dimsum Production Profits Using Linear Programs with The Simplex Method - Palahudin; Aida Komalasari aida; Aldi Humaedi; Apri setiawan AR; Fina Alfiani Fina; Nayla Salsabila Nayla (Journal Of Management Analytical and Solution (JoMAS), 2025)
The culinary industry, especially dimsum products in Indonesia, is experiencingrapid growth, which is accompanied by increasing public demand for deliciousand practical ready-to-eat food. This study aims to optimize dimsum productionprofits in a successful dimsum shop in Bogor, West Java, by using linearprograms and simplex methods. By analyzing data obtained from interviews andobservations, it can be known the factors that affect decision-making, the goalsto be achieved, and the limitations faced in production activities. This studyprovides guidance for Toko Dimsum Sukses to make the most of resources andincrease profitability, although there are some limitations, such as linearityassumptions and external variables that are not considered. This study revealsthat to achieve a maximum daily profit (Zmax) of Rp.19,800,000, a successfuldimsum shop needs to produce original dimsum (X1) 120 times and dimsummentai (X2) 1120 times.